(untitled) (Hekima Review, 2024)
Acursory look at the title might give the impression that this book is a treatise on the discernment of God's will. But it's not quite that! It is , rather a chronology of the exemplary lives of some key Jesuits of modern times, with a view to enabling the reader to be influenced by their tremendous fervor and so to make his or her own choice for Christ.